Survey on the Achievment Motivation of Atheletes Indonesian National Sport Committee (KONI) Bekasi City - Dini Nurfauziah; Dani Nur Riyadi; Aridhotul Haqiyah (Universitas Negeri Semarang, 2025)
The purpose of this study was to determine the level of achievement motivation among athletes of the Indonesian National Sports Committee (KONI) of Bekasi City in preparation for the 2025 West Java Provincial Sports Week (PORPROV XV) Qualification Round. The achievement motivation questionnaire was developed based on the Need for Achievement theory, consisting of 31 valid items with four dimensions: enthusiasm, self-confidence, perseverance, and discipline. Data were collected from 140 athletes consisting of pre-adolescent, adolescent, and adult categories, then analyzed using SPSS version 23. The results showed that in three dimensions namely enthusiasm, self-confidence, and determination, 139 athletes (99.29%) were in the high motivation category, while 1 athlete (0.71%) was in the low category. In the discipline dimension, 138 athletes (98.57%) were in the high category and 2 athletes (1.43%) were in the low category. Overall, these findings indicate that the majority of athletes have high and consistent achievement motivation in most dimensions, reflecting good psychological readiness to face competition. Although most athletes have high motivation, there are some athletes who need psychological reinforcement to achieve optimal consistency, so a comprehensive coaching program is very necessary. Overall, these findings reflect the psychological readiness and high commitment of athletes to achieve optimal performance in competitions.